Feasibility of respiratory synchronization for laser lithotripsy using a robotic retrograde intrarenal surgery system Zamenix™ in an in-vitro model - Joonhwan Kim; Chinnakhet Ketsuwan; Kyu-Seob Song; Jae-chul Kim; Joonyeong Kim; Hyeji Park; Dong-Soo Kwon; Joo Yong Lee; Sung Yong Cho (European Journal of Medical Research)
Abstract Objectives This study aims to investigate the improvement of stone fragmentation efficiency and safety in robotic-assisted retrograde intrarenal surgery (RIRS) that implements the respiratory motion synchronization using an in vitro model. Materials and methods Laser lithotripsy was performed in three groups: manual procedure (group M), robotic procedures without respiratory synchronization (group RNR), and robotic procedures with respiratory synchronization (group RR). The study assessed fragmentation time, laser time, number of mucosal contacts, and total energy used. Two surgeons having different experience of conventional RIRS (> 2500 and < 500) were participated. Results In overall results of the two surgeons, the fragmentation time significantly decreased to 74.8% in group RNR (P = 0.012) and 65.0% in group RR (P = 0.001), compared to group M. The laser time was significantly shorter in group RR compared to the group M (P = 0.003). The number of mucosal contacts was significantly reduced to 37.4% in group RNR (P = 0.048) and it was 34.0% in group RR, compared to group M. The total energy significantly decreased in group RR compared to group M (P = 0.011). There were no significant differences between group RR and RNR across all outcomes in the overall results of the two surgeons. For less experienced surgeon, the fragmentation time was significantly shorter in group RR compared to group RNR (P = 0.013). Conclusions Robotic-assisted RIRS resulted in reduced fragmentation time, laser time, mucosal contacts, and total energy compared to manual RIRS during laser lithotripsy. The incorporation of respiratory synchronization in robotic-assisted RIRS reduced laser time compared to manual RIRS and shortened the fragmentation time compared to the robotic-assisted RIRS without respiratory synchronization, particularly for less experienced surgeon. These initial results demonstrated the feasibility of robotic-assisted RIRS with respiratory synchronization, highlighting its potential to improve procedural efficiency and safety.